2019
DOI: 10.3389/fcimb.2019.00152
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and Nonsense Transcripts as Putative Viral Evasion Mechanisms

Abstract: Viral proteins encode numerous antiviral activities to modify the host immunity. In this article, we hypothesize that viral genomes and gene transcripts interfere with host gene expression using passive mechanisms to deregulate host microRNA (miRNA) activity. We postulate that various RNA viruses mimic or block binding between a host miRNA and its target transcript, a phenomenon mediated by the miRNA seed site at the 5′ end of miRNA. Virus-encoded miRNA seed sponges (vSSs) can potentially bind to host miRNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The rest of the transcripts are demarcated as noncoding RNAs, including microRNAs, which typically function post-transcriptionally to control the gene expression [ 69 ]. Various RNA viruses mimic or block the binding between a host miRNA and its target transcript, a phenomenon mediated by the miRNA seed site at the 5′ end of miRNA [ 70 ]. In past days, respiratory viral infections caused by influenza, rhinovirus, adenovirus, RSV, and coronaviruses can be related to aberrant host miRNA expression, and their effect on the host can results in cell apoptosis, inhibition of immunologic pathways, and downregulation of host antiviral responses [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rest of the transcripts are demarcated as noncoding RNAs, including microRNAs, which typically function post-transcriptionally to control the gene expression [ 69 ]. Various RNA viruses mimic or block the binding between a host miRNA and its target transcript, a phenomenon mediated by the miRNA seed site at the 5′ end of miRNA [ 70 ]. In past days, respiratory viral infections caused by influenza, rhinovirus, adenovirus, RSV, and coronaviruses can be related to aberrant host miRNA expression, and their effect on the host can results in cell apoptosis, inhibition of immunologic pathways, and downregulation of host antiviral responses [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the structure of viral miRNAs is similar to animal miRNAs due to the reliance on host enzymatic machinery for their production [121][122][123]. However, if their structures differ at all, for example as a result of non-canonical biogenesis pathways, this may lead to an absence of specific sequence features, such as 3 overhangs that sequencing adapters recognise and bind to during the library preparation protocols and within prediction software.…”
Section: Data Availability Statementmentioning
confidence: 99%
“… 11 , 12 According to recent reports, viral RNA may form complexes with host mRNAs and behave as miRs or rRNAs. 13 , 14 Evidence also supports that the miR biogenesis by host cells may provide an efficient antiviral response. 15 Several miRs have been identified as being differentially regulated in disease conditions and significantly correlate with elevated cytokine storms.…”
Section: Introductionmentioning
confidence: 92%
“…There are three main proposed mechanisms: the first option is that RNA-based viral genomes may either avoid being targeted by the cellular miRs expressed against virus infection or block the cellular miRs to regulate essential proteins in the main signaling pathways. , The second option is that viruses could synthesize their viral miRs to create a more favorable cellular environment to survive in the host cells . Third, viruses might manipulate cellular miRs to their advantage. , According to recent reports, viral RNA may form complexes with host mRNAs and behave as miRs or rRNAs. , Evidence also supports that the miR biogenesis by host cells may provide an efficient antiviral response . Several miRs have been identified as being differentially regulated in disease conditions and significantly correlate with elevated cytokine storms .…”
Section: Introductionmentioning
confidence: 99%